Investigating the role of neurotrophins in the development of pain responses in animal models of joint pain - Gowler, Peter (2018)
Background: The chronic joint disease osteoarthritis (OA) represents a significant global problem, not only at the present time, but also for the future. Characterised by articular cartilage degeneration, inflammation of the synovium, and subchondral bone changes, it is the chronic pain associated with OA which presents the most serious consequences. There is a clear need to understand the mechanisms under lying chronic joint pain, and to identify novel therapeutic targets. Two targets which may have therapeutic potential are BDNF and cordycepin. Objectives: The objectives of this thesis are two-fold; firstly to establish a slow progressing murine model of OA that is representative of post-traumatic OA, and secondly to investigate peripheral targets which may modulate chronic OA pain. Methods: Surgical destabilisation of the medial meniscus (DMM) was carried out in adult C57BL/6 mice. Weight bearing asymmetry and hindpaw withdrawal threshold were measured up to 16 weeks post-surgery. Joint pathology was then assessed post-mortem at 16 weeks post-surgery. Another cohort of adult C57BL/6 mice underwent a modified surgical destabilization of the medial meniscus. Pain behaviour and joint pathology outcomes were measured 16 weeks and 20 weeks post-surgery. Osteoarthritis was induced in adult male Sprague Dawley rats via intra-articular injection of monosodium iodoacetate (MIA) or vehicle (50ul 0.9 % saline. A second cohort of male Sprague Dawley rats underwent either meniscal transection (MNX) or sham surgery. Rats then received intra-articular injections of either trkB-fc or human IgG. Pain behaviour was tested up to 3 hours post injection. Adult C57BL/6 mice underwent DMM or sham surgery. Pain behaviour was measured up to 16 weeks post-surgery. From 14 weeks post-surgery mice were orally dosed with either cordycepin or vehicle every two days for two weeks. Joint pathology was then assessed post-mortem at 16 weeks post-surgery. Results:There was a significant increase in weight bearing asymmetry from 13 weeks post DMM surgery in C57BL/6 mice, but no changes in hindpaw withdrawal thresholds. There were also significant increases in chondropathy and synovitis at 16 weeks post-surgery. When the surgical induction of the DMM model was modified there were still significant changes in joint pathology, but no significant changes in pain behaviour. Intra-articular injection of TrkB/fc chimera in rats with established MIA induced joint pain was found to acutely reduce weight bearing asymmetry and increase ipsilateral hindpaw withdrawal thresholds. There was also a significant reduction in pain behaviour in rats with MNX established joint pain when TrkB/fc chimera was injected into the knee joint. Following systemic administration of cordycepin in mice with DMM induced joint pain there was a significant reduction in weightbearing asymmetry when compared to vehicle treated mice. There was also a significant reduction in DMM induced chondropathy, subchondral bone thickening, and osteophytosis in mice treated with cordycepin compared to vehicle treated mice. Conclusions: The changes in pain behaviour outcomes between the traditional and modified DMM, despite similar joint pathology outcomes, suggests a role for meniscal damage as a peripheral driver of OA pain. Localised injection of TrkB/fc chimera into the knee joint of rats with both MIA and MNX induced joint pain was found to acutely reverse joint pain. This implies that peripheral BDNF may be involved in mediating OA joint pain. Oral administration of cordycepin was found to reduce both pain behaviour and joint pathology changes in the DMM model in mice. These results suggest a role for local protein translation underlying both OA chronic pain and joint damage.